Využití vybraných terapií v dětských domovech pro děti do 3 let věku - Peřinová, Kateřina (Univerzita Pardubice, 2013)
The report is focused on children´s homes for children with serious health and social problems. There are 33 these organisations in the Czech Republic. It is well known, that children living in these institutions from neonatal age, suffer lack of incentives. This fact has great influence to personality development. Therapies could help them to obtain more social contacts and experience with another environment. Scientific aim was to find out, if these institutions use special therapy to support children´s psychomotor development. The questionnaire was used for the research. The main result was found out if children´s homes use therapies.
The use of chosen therapies in the children's homes for children under 3 years of their age
Keywords: children with serious health problem; abandoned children; children´s homes; animal therapy; music therapy